Investigations into the functioning of phytoplankton, zooplankton, kelp and benthic communities at the Prince Edward Islands - Attwood, Colin Graham (Department of Biological Sciences, 2016)
Abstract Several questions pertaining to the marine communities at the Prince Edward Islands are addressed. Firstly, the nature of the 'island-mass effect', and the cause of the frequently recorded diatom blooms in the area are examined. It had been suggested that the cause of the blooms is related to the presence of a Taylor Column-induced, low density, stationary eddy which stabilises the water column. On a cruise in April/May 1989, temperature, salinity, nutrients, chlorophyll and primary production were measured at 90 stations in a large grid centred on the islands. These, together with data collected on previous cruises, are used to show that the repeated occurrence of diatom blooms was not a result of nutrient enhancement. No evidence for light-limitation of phytoplankton was found. The evidence and theoretical basis which was used to predict the existence of a Taylor Column is questioned. An alternative hypothesis for explaining the blooms is presented. It is argued that these local blooms are simply the result of seeding by a dormant stock of diatom resting spores from the shallow sediments around the islands. This hypothesis hinges on three observations: (1) the blooms occur only over shallow sediments and are not a feature of the open ocean, (2) the species Chaetoceros radicans has been responsible for the bloom each time the cells were identified, and (3) C. radicans forms a rapidly sinking, heavily silicified, resting spore.